Expert System for Diagnosing Covid-19 Disease Using Method Forward Chaining - Fadli, Sofiansyah; Ashari, Maulana; Septiani, Ria; Saikin, Saikin; Sudyana, Didik (JISA(Jurnal Informatika dan Sains), 2024)
December 2019 was the beginning of cases that hit the Wuhan area, increasing cases of Covid-19 in China every day and increasing from January to February 2020. Initially reports came from the Hubei area and surrounding provinces, and the reports that came increased to the provinces around China, there were 86 other cases reported from various parts of the country, including Indonesia. Indonesia's first Covid-19 disease reportedly entered on March 2, 2020, there were two cases. The latest information is published on the official WHO website (World Health Organization) it was recorded that from January 3, 2020 to March 18, 2022 in Indonesia, there were 5,948,610 people who were recorded as positive for Covid-19 and 153,411 people were confirmed to have died. Diagnosing Covid-19 is the job of experts or specialists who have experience and knowledge in this field. An alternative that can help people who are not experts in diagnosing Covid-19 is an expert system. The forward chaining method was chosen because it is a forward tracking technique that is sorted according to the number of facts and ends with a conclusion. Forward Chaining is a method inference engine where this method compares facts and statements and will start from the left first (IF). Where, reasoning will start from the facts and then test the validation of the hypothesis (THEN). This research was conducted to make it easier for non-experts to diagnose Covid-19 with this expert system, and to be able to provide solutions after a successful diagnosis.